2019
DOI: 10.1177/1082013219889439
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ginger rhizome and refrigerated storage time on the quality of pasteurized canned meat

Abstract: The effect of ginger rhizome, in comparison with sodium ascorbate and butylated hydroxytoluene, and storage time at 5℃ on the quality of pasteurized canned meat was studied. Ginger rhizome was as effective as sodium ascorbate in inhibiting lipid oxidation. The canned meat with ginger rhizome was characterized by a lighter color and a lower contribution of redness than the remaining products. It was also characterized by the lowest hardness, springiness, and chewiness. In a sensory evaluation, meat with ginger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In summary, the addition of ginger to pork meatloaf reduced hardness and springiness, and improved chewiness. These results are consistent with the findings of Draszanowska et al [ 7 ] who analysed pasteurised canned meat with 1.5% addition of ginger rhizome.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In summary, the addition of ginger to pork meatloaf reduced hardness and springiness, and improved chewiness. These results are consistent with the findings of Draszanowska et al [ 7 ] who analysed pasteurised canned meat with 1.5% addition of ginger rhizome.…”
Section: Resultssupporting
confidence: 93%
“…Draszanowska et al [ 7 ] reported that 1.5% ginger-rhizome addition to pasteurised canned pork meat was as effective as sodium ascorbate in inhibiting oxidative changes during refrigerated 50 days storage. Singh et al [ 22 ] observed that 3% addition of ginger paste to chicken meat emulsion was as effective as 2% addition of garlic paste, but less effective than 0.2% addition of clove powder in inhibiting oxidative changes during refrigerated storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter of redness in nitrite‐free canned meat was found to be significantly lower than in nitrite‐containing products (Ferysiuk & Wójciak, 2020). Additionally, the addition of ginger rhizome resulted in a lighter color and a lower redness contribution to pork canned meat (Draszanowska et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the use of meat from cull chickens for the production of sausages, added with ginger extract, Reshi et al (2017) observed an improvement in physicochemical and microbiological quality, with acceptable changes in sensory characteristics, during 15 days of storage at 4ºC, considering that the use of ginger extract can be an alternative for the conservation of sausages made from chicken meat. Similarly, Draszanowska et al (2020) evaluated the use of ginger when comparing the addition of its rhizome in a formula containing 1% water and 1.5% of peeled and grated rhizome with the addition of sodium ascorbate, a synthetic preservative used by the food industry in canned pork meat (Draszanownska et al, 2020). It was observed that during days 0, 20 and 40, there was a similar antioxidant effect between the samples with the addition of ginger rhizome and the samples with the addition of sodium ascorbate, demonstrating that the application of ginger as a preservative for canned pork meat can be promising (Draszanownska et al, 2020).…”
Section: Vegetable Extracts As Preservatives In Meat and Meat Productsmentioning
confidence: 99%